Antagonism of Ca2+ Influx via L-Type Ca2+ Channels Mediates the Vasorelaxant Effect of Catharanthus roseus-Derived Vindorosine in Rat Renal Artery - Wu, Xiao-Lin; Cheang, Wai San; Zhang, Dong-Mei; Li, Yong; Lau, Chi-Wai; Wang, Guo-Cai; Huang, Yu; Ye, Wen-Cai (Planta Medica, 2014)
Catharanthus roseus is a traditional herbal medicine used in Asian and African countries for the treatment of various diseases including hypertension. The present study examined possible cellular mechanisms for the relaxation of rat renal arteries induced by vindorosine extracted from C. roseus. Intrarenal arteries were isolated from 200–300 g male Sprague-Dawley rats and treated with different pharmacological blockers and inhibitors for the measurement of vascular reactivity on a Multi Myograph System. Fluorescence imaging by laser scanning confocal microscopy was utilized to determine the intracellular Ca2+ level in the vascular smooth muscles of the renal arteries. Vindorosine in micromolar concentrations relaxes renal arteries precontracted by KCl, phenylephrine, 11-dideoxy-9α,11α-epoxymethanoprostaglandin F2α, and serotonin. Vindorosine-induced relaxations were unaffected by endothelium denudation or by treatment with the nitric oxide synthase inhibitor NG-nitro-L-arginine methyl ester hydrochloride, the guanylyl cyclase inhibitor 1H-[1, 2, 4]oxadiazolo[4,3-a]quinoxalin-1-one, the cyclooxygenase inhibitor indomethacin, or K+ channel blockers such as tetraethylammonium ions, glibenclamide, and BaCl2. Vindorosine-induced relaxations were attenuated in the presence of 0.1 µM nifedipine (an L-type Ca2+ channel blocker). Vindorosine also concentration-dependently suppressed contractions induced by CaCl2 (0.01–5 mM) in Ca-free 60 mM KCl solution. Furthermore, fluorescence imaging using fluo-4 demonstrated that 30 min incubation with 100 µM vindorosine reduced the 60 mM KCl-stimulated Ca2+ influx in the smooth muscles of rat renal arteries. The present study is probably the first report of blood vessel relaxation by vindorosine and the possible underlying mechanisms involving the inhibition of Ca2+ entry via L-type Ca2+ channels in vascular smooth muscles.
Keywords: Catharanthus roseus; Apocynaceae; vindorosine; Ca2+ channel; vasorelaxation; renal artery